STRATEGI PARTAI POLITIK DALAM MERAIH SUARA DI PEMILU TAHUN 2024 (Studi Partai Gerindra Kabupaten Tulungagung): STRATEGI PARTAI POLITIK DALAM MERAIH SUARA DI PEMILU TAHUN 2024 (Studi Partai Gerindra Kabupaten Tulungagung) - Rahayu, Anggun Vera; Rahayu, Nanda Putri; Wardani, Alfio Triana; Purnawati, Laily (CV Kalimasada Group, 2024)
This journal examines the campaign strategies employed by the Gerindra Party in the 2024 elections in Tulungagung. The study aims to analyze the effectiveness of various approaches implemented by the party to garner support from the local electorate. Utilizing a qualitative methodology, the research involves interviews with party officials, analysis of campaign materials, and observation of grassroots activities. Key strategies identified include personalized outreach through community engagement, the use of social media platforms to amplify messages, and the focus on local issues that resonate with voters. Furthermore, the study highlights the importance of coalition-building with local organizations to enhance credibility and broaden the party's reach. This research contributes to the understanding of regional political dynamics and the evolving nature of campaign strategies in Indonesia.